Penetapan Kadar Beta Karoten pada Ekstrak Aseton Buah Blewah (Cucumis Melo L.) Berdasarkan Tingkat Kematangan Buah - Dedi Nofiandi; Roslinda Rasyid; Aulia Maizola (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Blewah fruit (Cucumis melo L.) is a plant that contains β-carotene. β-caroten is a natural organic pigment that is yellow, orange and red orange brown which is found in vegetables and fruits. The research was also aimed to see difference of beta caroten on the Blewah fruit (Cucumis melo L.) based on the level of maturity of the fruit namely law and ripe. Each sample was extracted by using maceration method using aceton as as solvent, more over. Aceton extract was saponified matter and re-extracted using petroleum eter. Qualitative test using thin layer chromatography method with eluent n-hexane: aseton (9:1) and quantitative test using uv-vis spectrophotometry method at a maximum absorption wavelength of 479 nm. The qualitative test showed that law blewah and ripe blewah identified as containing beta caroten with an Rf 0,7. The quantitative analysis showed that beta caroten in young blewah and ripe fruit blewah 0,237 % b/b ± 0,0009 % b/b with a coefficient of variation 0,3861 % and 0,387 % b/b ± 0,0009 % b/b with a coefficient of variation 0,2366 %. The results show higest level of beta caroten obtained ripe fruit blewah followed by young blewah. The results of the residual standard deviation (SBr) 0,00414 µg/mL, limit of detection (BD) 2,28308 µg/mL and limit of quantitation with the regression equation y = -0,0012 + 0,00544x. Analysis method using t indenpenden (SPSS 25) showed the significant difference in each young blewah and ripe fruit blewah (p<0,005). Based on the levels obtained, the ripe blewah fruit can be used as a source of vitamin A.